2016
DOI: 10.1007/s00392-016-1019-4
|View full text |Cite
|
Sign up to set email alerts
|

Fractional flow reserve-guided coronary angioplasty using paclitaxel-coated balloons without stent implantation: feasibility, safety and 6-month results by angiography and optical coherence tomography

Abstract: BackgroundPercutaneous coronary interventions (PCI) with drug-coated balloons (DCB) might be a promising trade-off between balloon angioplasty and drug-eluting stents, since DCB inhibit neointimal proliferation and limit duration of dual antiplatelet therapy. We investigated the safety, feasibility, and 6-month results of fractional flow reserve (FFR)-guided use of the paclitaxel-coated SeQuent Please® balloon without stenting for elective PCI of de novo lesions.Methods and resultsIn 46 patients (54 lesions) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Moreover, without a mechanical scaffold, using a DCB removes the technical burden of treating ISR and allows patients to receive non-invasive magnetic resonance examination. In our study, as for coronary artery disease,8 the DCB seems to play a significant role in vascular remodeling and patency improvement for intracranial arteries. As shown in figure 3, residual stenosis of approximately 50% of the basilar artery was found after DCB dilatation.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, without a mechanical scaffold, using a DCB removes the technical burden of treating ISR and allows patients to receive non-invasive magnetic resonance examination. In our study, as for coronary artery disease,8 the DCB seems to play a significant role in vascular remodeling and patency improvement for intracranial arteries. As shown in figure 3, residual stenosis of approximately 50% of the basilar artery was found after DCB dilatation.…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, when the same criteria of lesion preparation using FFR were ap-plied, DCB treatment showed persistent anatomical and physiological patency with plaque redistribution and vessel remodeling without chronic elastic recoil or plaque compositional change during follow-up [38]. Similarly, recent European data showed that if it was determined that there was sufficient lesion preparation with residual stenosis < 40%, FFR > 0.80 and no severe dissection, DCB treatment was feasible and safe with a trend toward positive vessel remodeling without lumen loss at 6 months [40].…”
Section: Optimal Lesion Preparationmentioning
confidence: 88%
“…In addition, using intravascular ultrasound (IVUS) and optical coherence tomography (OCT), the investigators suggested that DCB restores coronary blood flow by means of plaque modification, causing an increment in the minimal lumen area [38,39]. Recent European data also showed that the FFR-guided DCB-only approach of de novo lesions (cutoff value of FFR: 0.80) was feasible and safe in stable CAD, showing positive remodeling without lumen loss by OCT at 6 months [40]. Another study showed that the safety and efficacy of DCB was comparable with DES when the cut-off value of FFR was 0.75 after balloon angioplasty [41].…”
Section: De Novo Lesionmentioning
confidence: 99%
“…OCT showed an increased mean luminal diameter and volume at follow-up in addition to the sealing of 66% of dissections. The OCTOPUS II study again through an FFR-guided approach with OCT analysis also showed positive luminal gain, healing of dissections and a lack of thin-cap fibroatheromas [ 34 ].…”
Section: Patient Characteristicsmentioning
confidence: 99%